2
$\begingroup$

I'm clearly making a silly mistake here, but I can't see it.

EDIT: I missed brackets when typing out the expression to calculate. Apologies for timewasting.

I have the equation $(2x + 3)(5x + 1)=0$. Setting each bracket to $0$ I get my roots as $x=-\frac32$ and $x=-\frac15$.

To confirm my working I expand the brackets as $10x^2 + 17x + 3 = 0$. I then see my coefficients are $a=10$, $b=17$, and $c=3$.

Putting this into the formula I get $x = \frac{-17 \pm \sqrt{17^2 - 4\times10\times3}}{2\times10}$, which gives $x=-20$ and $x=-150$.

I really can't see what I've done wrong here. Any help appreciated. Thank you.

$\endgroup$
  • $\begingroup$ It's hard to know where your mistake is if you don't show all your calculations... $\endgroup$ – DonAntonio May 23 '16 at 21:48
  • $\begingroup$ I just typed it into google (-17 +sqrt(17**2 - 4*10*3)) / 2*10 EDIT: missed brackets on 2*10 $\endgroup$ – Ashiataka May 23 '16 at 21:56
  • $\begingroup$ @As That doesn't help. The radical expression is 169, for example. Who knows what you got. $\endgroup$ – DonAntonio May 23 '16 at 22:33
  • $\begingroup$ It was dividing by 2 then multiplying by 10 rather than dividing by 20. $\endgroup$ – Ashiataka May 23 '16 at 22:34
4
$\begingroup$

$$ \begin{aligned} x_{1,2}&=\frac{-17\pm\sqrt{17^2-4\cdot 10\cdot 3}}{2\cdot 10}\\[6pt] &=\frac{-17\pm\sqrt{169}}{20}\\[6pt] &=\frac{-17\pm 13}{20}\\[6pt] &\implies x_{1}=\frac{-30}{20}=-\frac{3}{2},\quad x_{2}=\frac{-4}{20}=-\frac{1}{5} \end{aligned} $$

$\endgroup$
0
$\begingroup$

$$17^2-4\cdot10\cdot3\cdot=169=13^2\implies x_{1,2}=\frac{-17\pm13}{20}=-\frac32,\,-\frac15$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.